Zooplankton community and their relationship with water quality in São Paulo State reservoirs - De-Carli, Bruno P. [UNESP]; De Albuquerque, Felícia P. [UNESP]; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo (FapUNIFESP (SciELO), 2018)
Zooplanktonic communities are important components in trophic chain considering primary producers and other levels. In addition, some species are sensitive or tolerant to organic pollution. Here we test the hypothesis that species composition varies according to the eutrophication gradient. We sought to establish which environmental factors are responsible for the variation of the species distribution. This study aimed to characterize zooplankton community and to establish a link between water quality in São Paulo State reservoirs. Samples were collected through vertical hauls with plankton net (68 μm) in seven water bodies. All specimens were identified with specific literature and counted in Sedgwick rafter chamber. Abiotic and biotic data were analyzed by a canonical correspondence analysis. A total of 67 taxa was identified, being Rotifera predominant. The reservoirs exhibited eutrophic conditions mainly Salto Grande, Barra Bonita and Broa. The results point out the rotifers Trichocerca longiseta (Schrank, 1802), Hexarthra sp., Brachiounus spp. and Keratella tropica (Apstein, 1907) followed eutrophication gradient. Additionally, microcrustaceans such as Notodiaptomus, Mesocyclops, Metacyclops and Diaphanossoma occurred in eutrophic reservoirs. On other hand, the cladocerans Ceriodaphnia cornuta (Sars, 1886) and Bosminopsis deitersi Richard, 1895 were considered indicators of better water quality due to relationship with transparency. The results point out that some indicator species are effective in environmental monitoring without reject physico-chemical and biological analysis.
Comunidade zooplanctônica e sua relação com a qualidade da água em reservatórios do Estado de São Paulo
Keywords: Eutrophication; Water quality; Zooplankton